Capillary hemangioma or pyogenic granuloma: A diagnostic dilemma - M M Rachappa; M N Triveni (Wolters Kluwer Medknow Publications, 2010)
Pyogenic granulomas and hemangiomas of oral cavity are well-known benign lesions. Although pyogenic granuloma is known to show a striking predilection for the gingiva and capillary hemangioma for lips, check, and tongue, palatal occurrence of these lesions is extremely rare. The clinical diagnosis of such an uncommon occurrence can be quite challenging as they sometimes may mimic more serious lesions such as malignancies. The purpose of this article is to report an unusual case of benign tumor occurring on hard palate which was clinically diagnosed as pyogenic granuloma and histopathologically as capillary hemangioma.